Educational Activities Concerning Folk/Popular Culture in Greek Primary School Websites - Kakampoura, Rea; Katsadoros, George; Nounanaki, Αphrodite; Kolokythas, Dimitris (European Scientific Journal, ESJ, 2017)
Folk/Popular culture comprises a many-sided and complex term, existing in both its traditional (Folk) and contemporary dimension (Popular). Many of its aspects can be traced in Primary Education school books, but in many cultural school displays as well. Student participation in cultural oriented activities encourages enculturation, the awareness of belonging in one or many cultural groups, and, successively, an understanding of one’s cultural identity. This article presents the results of research conducted all over Greece concerning educational programs and activities about folk/popular culture as shown in the websites of Greek public and private Primary Schools and Kindergartens, utilizing online data collection.